Decreased levels of genuine large free hCG alpha in men presenting with abnormal semen analysis - Plas Eugen; Lindner Herbert; Gruschwitz Matthias; Gerth Regine; Zenzmaier Christoph; Berger Peter (BMC, 2011)
Abstract Background The pregnancy hormone human chorionic gonadotropin (hCG) and its free subunits (hCG alpha, hCG beta) are produced in the male reproductive tract and found in high concentrations in seminal fluid, in particular hCG alpha. This study aimed to elucidate changes in peptide hormone profiles in patients showing abnormal semen analyses and to determine the genuineness of the highly abundant hCG alpha. Methods Seminal plasma was obtained from 45 male patients undergoing semen analysis during infertility workups. Comprehensive peptide hormone profiles were established by a panel of immunofluorometric assays for hCG, hCG alpha, hCG beta and its metabolite hCG beta core fragment, placental lactogen, growth hormone and prolactin in seminal plasma of patients with abnormal semen analysis results (n = 29) versus normozoospermic men (n = 16). The molecular identity of large hyperglycosylated hCG alpha was analyzed by mass-spectrometry and selective deglycosylation. Results hCG alpha levels were found to be significantly lower in men with impaired semen quality (1346 +/- 191 vs. 2753 +/- 533 ng/ml, P = 0.022). Moreover, patients with reduced sperm count had reduced intact hCG levels compared with normozoospermic men (0.097 +/- 0.022 vs. 0.203 +/- 0.040 ng/ml, P = 0.028). Using mass-spectrometry, the biochemical identity of hCG alpha purified from seminal plasma was verified. Under non-reducing conditions in SDS-PAGE, hCG alpha isolated from seminal plasma migrated in a manner comparable with large free hCG alpha with an apparent molecular mass (Mr, app) of 24 kDa, while hCG alpha dissociated from pregnancy-derived holo-hCG migrated at approximately 22 kDa. After deglycosylation with PNGase F under denaturing conditions, all hCG alpha variants showed an Mr, app of 15 kDa, indicating identical amino acid backbones. Conclusions The findings indicate a pathophysiological relevance of hCG, particularly its free alpha subunit, in spermatogenesis. The alternative glycosylation pattern on the free large hCG alpha in seminal plasma might reflect a modified function of this subunit in the male reproductive tract.